PEMBERDAYAAN ANAK PANTI ASUHAN AN-NAHL DAN YAUMIHA DI KABUPATEN SRAGEN MELALUI KETRAMPILAN BETERNAK AYAM RAS PETELUR - Dewanti, Ratih; Sudiyono, Sudiyono (LPPM UNS, 2017)
IbM activity was held at the An-Nahl and YAUMIHA orphanage Sragen. The method were counseling, training, and mentoring maintenance layer, providing complete equipment, marketing and management administration and composting. The target of outcomes are resulting child in orphanage which economically independent, and sustainable of layer egg production. There were 96 bateray cages, place of feed, nipple drinker, eggtray, 96 Brown Leghorn pullet and layer feed given to orphanage. From the results of quisioner counseling increased the value of correct answers (knowledge increased) after counseling was 219 points compared before the 118 point extension. Peak production of eggs at 30 weeks of layer age of 98%. Sales of perkilo eggs with the price of Rp.17.000-Rp.20.000/kg. Business analysis with a net profit of Rp. 23.000,-per day. Through these activities, students' abilities and skills An-Nahl and YAUMIHA orphanage have increased and are expected to be economically self-sufficient. The next plan is for both the partners increase the population of layer by buying pullet in order to expand the business.Keywords: Layer, Farming Skills, Orphanage, An-Nahl and YAUMIHA